Total phenolic compound content, antioxidant property and quality changes of the southern sour curry paste, keang-hleung, as affected of garcinia, Garcinia atroviridis, salt during storage - Preeyaporn Promjiam; Sunisa Siripongvutikorn; Santad Wichienchot; Worapong Usawakesmanee (Syiah Kuala University, 2012)
Southern sour curry or Keang-hleung soup is traditional popular spicy-sour curry consumed not only in southern part of Thailand. The ingredients used in the paste are turmeric rhizome, garlic, shallot and chili which have been reported as a source of antimicrobial and antioxidant compounds. The total phenolic compound content and the antioxidant activities of Keang-hleung paste with and without garcinia were monitored. It was found the total phenolic compound content of the basic paste without the garcinia, garcinia Keang-hleung paste, garcinia- Keang-hleung paste without salt and the garcinia extract determined by the Folin-Ciocalteu method were 0.236±0.039, 0.245±0.009, 0.639±0.006 and 0.457±0.030 g GAE/100g dw respectively. The DPPH (2,2-diphenyl-1-picrylhydrazyl) activity of the basic paste, garcinia Keang-hleung paste, garcinia- Keang-hleung paste without salt and the garcinia extract were 0.658±0.010, 0.736±0.047, 0.818±0.147 and 0.018±0.001 g GAE/100g dw, while the ferric reducing power were 0.405±0.028, 0.590±0.030, 1.150±0.044 and 0.015±0.001 g GAE/100g dw, respectively. Total viable count (TVC) of all paste sample were in range of 102-103 log cfu/g. Yeast and mold counts of basic and garcinia Keang-hlueng paste were less than 30 cfu/g during storage. While, yeast and mold counts of garcinia Keang-hlueng paste without salt were less than 102 cfu/g during storage. Lactic acid bacteria counts of garcinia Keang-hlueng paste were less than 30 cfu/g during storage. While, lactic acid bacteria counts of the basic and garcinia Keang-hlueng paste without salt were less than 102 log cfu/g during storage. Moreover, Staphylococcus aureus, Bacilluus cereus, Clostridium perfringens, Salmonella, Escherichia coli and coliforms were not detected in all treatments throughout the storage period. All paste samples were accepted by panelist with higher border line score. However, addition of garcinia in paste tended to obtain higher score in all attributes compared with the basic paste